Evaluation of various blended fertilizer types and rates for better maize (Zea mays) crop production in Yeki woreda, Sheka Zone, South West Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2023)
Appropriate fertilization methods for a particular crop based on real limiting nutrients and crop demands are cost-effective and wise utilization of fertilizers for long-term agricultural productivity. An experiment was done to assess alternative fertilizer types and rates for better maize production during main cropping season of 2018 and 2019. The fertilizers were set depending on the study area's limiting nutrients, which include NPS and NPSB at various rates. There are seven treatments in the experiment: (1)no fertilizer; (2) NPS: 69N, 54P2O5, 10S; (3) NPS: 92N, 72P2O5, 13S; (4) NPS: 115N, 90P2O5, 17S; (5) 69N, 54P2O5, 10S, 1.05B NPSB; (6) 92N, 72P2O5, 13S, 1.4B NPSB and (7) 115N, 90P2O5, 17S, 1.7B NPSB. Treatments were placed out in a randomized complete block design and replicated three times on two farmers' fields. The study showed that using NPS mixed fertilizer had a substantial impact on maize output when compared to the control. Treatment 2 (NPS; 69N, 54p2o5, 10S) yielded significantly greater maize yield over control at (P